099 Safety and effectiveness of dimethyl fumarate in multiple sclerosis patients treated over 5 years. Issue 6 (27th May 2022) - Giles, Kathryn; Balashov, Konstatin; Macdonell, Richard; Windsheimer, Joerg; Okai, Annette; Martinez, Mikel; Mokliatchouk, Oksana; Lyons, Jennifer; Kapadia, Shivani
Abstract : Introduction: In clinical studies, delayed-release dimethyl fumarate (DMF) demonstrated a favorable benefit-risk profile in patients with relapsing-remitting multiple sclerosis (MS). Real-world studies enable char- acterization of risks that may emerge with long-term exposure in clinical practice. ESTEEM (NCT02047097 ) is an ongoing 5-year study characterizing real-world long-term safety and effectiveness of routinely pre- scribed DMF in MS patients. Methods: Patients treated with DMF were recruited from 380 sites. The primary objective was to determine incidence, type, and pattern of serious adverse events (SAEs), and AEs leading to DMF discontinuation. Results: As of April 3, 2019, 5804 patients had ≥1 dose of DMF. SAEs were experienced by 245 (4.8%) patients, with infections (n=64; 1.3%) and nervous system disorders (n=35; <1%) the most common. There were 1676 (33.0%) permanent treatment discontinuations. Annualized relapse rate over the period of up to 5 years was significantly lower than in the year prior to baseline (risk reduction 88.6% [95% confidence interval: 87.7–89.4]; P<0.0001). Conclusions: These results reveal low risk of SAE and beneficial therapeutic effects over up to 5 years of real-world DMF use. Updated safety and efficacy results for DMF patients in the United Kingdom will be presented. Support.Biogen. Disclosures: Included on the poster. Ben.newth@biogen.com